2019
DOI: 10.1021/acschemneuro.9b00232
|View full text |Cite|
|
Sign up to set email alerts
|

Orobol: An Isoflavone Exhibiting Regulatory Multifunctionality against Four Pathological Features of Alzheimer’s Disease

Abstract: We report orobol as a multifunctional isoflavone with the ability to (i) modulate the aggregation pathways of both metal-free and metal-bound amyloid-β, (ii) interact with metal ions, (iii) scavenge free radicals, and (iv) inhibit the activity of acetylcholinesterase. Such a framework with multifunctionality could be useful for developing chemical reagents to advance our understanding of multifaceted pathologies of neurodegenerative disorders, including Alzheimer’s disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
(56 reference statements)
0
15
0
Order By: Relevance
“…33,38 A strategy has been the search for such bifunctional chelators among naturallyoccurring compounds, and flavonoid compounds have been shown to interact with amyloidogenic peptides and arrest or redirect aggregation pathways. [39][40][41][42][43][44][45][46] For example, the green tea extracts (-)epigallocatechin-3-gallate (EGCG) and myricetin inhibit metal-induced Aβ40 aggregation by forming EGCG-metal-Aβ40 complexes. 39,47 We and others have previously found that the naturally-occurring biflavonoids including amentoflavone (AMF) potently attenuate Aβ aggregation and cytotoxicity, [48][49][50] however the metal-chelating ability of AMF and its effect on Aβ aggregation in presence of metal ions has not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…33,38 A strategy has been the search for such bifunctional chelators among naturallyoccurring compounds, and flavonoid compounds have been shown to interact with amyloidogenic peptides and arrest or redirect aggregation pathways. [39][40][41][42][43][44][45][46] For example, the green tea extracts (-)epigallocatechin-3-gallate (EGCG) and myricetin inhibit metal-induced Aβ40 aggregation by forming EGCG-metal-Aβ40 complexes. 39,47 We and others have previously found that the naturally-occurring biflavonoids including amentoflavone (AMF) potently attenuate Aβ aggregation and cytotoxicity, [48][49][50] however the metal-chelating ability of AMF and its effect on Aβ aggregation in presence of metal ions has not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…Nam et al . reported multiple reactivities of orobol toward the pathological factors found in AD, including metal‐free Aβ 42 , metal–Aβ 42 , free radicals, and acetylcholinesterase 64,65 . Notably, orobol impacted the aggregation of both metal‐free and metal‐associated Aβ 42 .…”
Section: Impact Of Flavonoids With a Catechol Or Pyrogallol Group On mentioning
confidence: 99%
“…Orobol , as depicted in Figure 4(a), that is an isoflavone with a catechol moiety was evaluated for its reactivity against metal‐free and metal‐induced Aβ aggregation 64,65 . Nam et al .…”
Section: Impact Of Flavonoids With a Catechol Or Pyrogallol Group On mentioning
confidence: 99%
“…27,28 Oro was found to interact with metal ions, alter the aggregation of both metal-free and metal-bound Ab, scavenge free radicals, and inhibit the catalytic activity of AChE. 29,30 The 12 avonoids enumerated in Fig. 1 include three different classes, namely avonols (row 1), avones (row 2), and iso-avones (row 3), that offer signicant structural variance.…”
Section: Rational Selectionmentioning
confidence: 99%